Recovery of zinc and other valuable metals from zinc leach residue by top blowing fuming method. (1st September 2013) - Wang, X. Q.; Xie, K. Q.; Ma, W. H.; Yang, M. Y.; Zeng, P.; Cao, Y. C.
Abstract : In this paper, comprehensive utilisation of hydrometallurgy zinc residue, goethite especially, was proposed. The raw material used in this study was mixed residue while the mass ratio of goethite and lead-silver residue was fixed at 4:1. Based on the characters of mixed residue, the top blowing fuming method was taken by using induction furnace. The effects of parameters such as CaO/SiO2 (0·61-0·91), C/feed mass ratio (18-26%) and reduction time (20-60 min) had been studied. Under the optimum conditions (CaO/SiO2 = 0·71; C/feed mass ratio of 24%; reduction time of 50 min), the average fuming efficiency of zinc, lead and sliver in the mixed residue could reach up to 97·2, 98·1 and 82% respectively.